Survivors of childhood cancer in Latin America: Role of foundations and peer groups in the lack of transition processes to adult long‐term follow‐up - Nuria Rossell; María Fernanda Olarte‐Sierra; Julia Challinor (Cancer Reports, 2022)
Abstract Background Over the last decade, the population of childhood cancer survivors has rapidly increased in Latin America, opening a long chapter of challenges for healthcare providers in these countries to provide follow‐up and adult care. Aim In the process of exploring childhood cancer parent and patient engagement in resource‐limited settings, we highlight the challenges faced by Latin American survivors from El Salvador, Mexico, and Peru as they transitioned from receiving cancer treatment to life as a cancer survivors. Methods and Results Focus group discussions and interviews were performed as part of a larger qualitative study involving 10 low and middle‐income countries in four continents regarding patient and caregiver engagement in childhood cancer treatment. We present the results of the Latin‐American survivors and their experiences finishing treatment and life outside the pediatric oncology follow‐up system. Themes regarding a) losing eligibility for pediatric surveillance and care, b) the importance of peer survivors, and c) the need for giving back were part of their stories. Conclusion We suggest that given the lack of organized support from healthcare systems and providers for survivors' proper transition into adult‐centered care, foundations and non‐governmental organizations can provide transitional support, offer space for guidance/information, and work towards collaboration among systems for future integrated programs.